Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1097/ana.0000000000000584
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Glucose and Lactate Levels After Subarachnoid Hemorrhage: A Multicenter Retrospective Study

Abstract: Background: In patients with subarachnoid hemorrhage (SAH), abnormalities in glucose and lactate metabolism have been described using cerebral microdialysis. Glucose and lactate concentrations in cerebrospinal fluid (CSF) are more easily accessible, but scarce data are available in this setting. The aim of this study is to assess the relationship of CSF glucose and lactate with blood concentrations and with unfavorable neurological outcome after SAH. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…This leads to mitochondrial impairment, inflammatory or oxidative reactions, ionic gradient breakdown, glutamate-mediated excitotoxicity, stress signaling and finally to cell deaths [50]. After SAH, decreasing CSF glucose-to-lactate ratios were reported to be accompanied by unfavorable outcomes [51], but the role of extracellular lactate is still controversial if the lactate supports basal metabolism in neurons or contributes to neurotransmission activity per se [52,53]. Recently, it has been revealed that neurons and glia orchestrate a metabolic reaction to sustain energy demands and the redox balance of neuronal activities or cause post-stroke brain injuries such as aquaporin 4-medated brain edema and neuronal apoptosis, which may be reduced by hypothermia-induced suppression of metabolic activity [50,[53][54][55][56].…”
Section: Possible Mechanisms Of Ebi Development After Sahmentioning
confidence: 99%
“…This leads to mitochondrial impairment, inflammatory or oxidative reactions, ionic gradient breakdown, glutamate-mediated excitotoxicity, stress signaling and finally to cell deaths [50]. After SAH, decreasing CSF glucose-to-lactate ratios were reported to be accompanied by unfavorable outcomes [51], but the role of extracellular lactate is still controversial if the lactate supports basal metabolism in neurons or contributes to neurotransmission activity per se [52,53]. Recently, it has been revealed that neurons and glia orchestrate a metabolic reaction to sustain energy demands and the redox balance of neuronal activities or cause post-stroke brain injuries such as aquaporin 4-medated brain edema and neuronal apoptosis, which may be reduced by hypothermia-induced suppression of metabolic activity [50,[53][54][55][56].…”
Section: Possible Mechanisms Of Ebi Development After Sahmentioning
confidence: 99%
“…For hyperglycemia after SAH, the effects of insulin treatment are not satisfied even with a high risk of hypoglycemia [ 8 ]. Targeted treatment of central IR seems to be a better way to improve energy metabolism disorders with a lower risk of hypoglycemia [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glucose transport and metabolism can serve as important regulatory points in the early apoptotic cascade [6]. A number of studies have shown that SAH patients with or without a history of diabetes will have transient hyperglycemia after bleeding, which seriously affects the prognosis [7][8][9]. Researchers proposed that insulin resistance (IR) after SAH was the direct cause of this phenomenon [9,10], but the mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with poor prognosis, the types and concentrations of amino acids in the CSF were increased, and phospholipid biosynthesis, steroid biosynthesis and fatty acid metabolism were up‐regulated (Li et al., 2019). Taccone et al performed metabolomic analysis of CSF from SAH patients and found that a low glucose/lactate ratio was associated with poor prognosis (Taccone et al., 2020). There are two major sources of glutamate in CSF after SAH.…”
Section: Csf Circulation Pathwaymentioning
confidence: 99%